2012
DOI: 10.1111/j.1447-0594.2011.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations of nutritional intake to age, sex and body mass index in Japanese elderly patients with type 2 diabetes: The Japanese Elderly Diabetes Intervention Trial

Abstract: Aim:To determine the status of nutritional intake in elderly Japanese patients with type 2 diabetes aged 65 years or older, and to clarify relations of nutritional intake to age, sex and body mass index (BMI).Design: Clinical parameters and nutritional intake were investigated and compared in 912 (417 men, 495 women) elderly Japanese patients with type 2 diabetes registered to the Japanese Elderly Diabetes Intervention Trial. Results:The mean daily energy intake of patients was 1802 kcal in men and 1661 kcal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…The detailed report on nutrition as a whole is reported in the present issue of the journal by Yoshimura et al and Kamada et al 13,14 In these reports, using the data of food intake that classified food into 16 classes, multivariable analysis was carried out, and from the dietary pattern obtained, the relationship to mortality was studied. Although the study design for the J-EDIT was a randomized control study by two groups, in which elderly diabetes patients were randomly allocated to standard therapy or intensive therapy, 12 there was no significant difference in the distribution of dietary patterns in the two groups (data not shown); therefore, we combined the two groups and analyzed them as a single cohort in the present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed report on nutrition as a whole is reported in the present issue of the journal by Yoshimura et al and Kamada et al 13,14 In these reports, using the data of food intake that classified food into 16 classes, multivariable analysis was carried out, and from the dietary pattern obtained, the relationship to mortality was studied. Although the study design for the J-EDIT was a randomized control study by two groups, in which elderly diabetes patients were randomly allocated to standard therapy or intensive therapy, 12 there was no significant difference in the distribution of dietary patterns in the two groups (data not shown); therefore, we combined the two groups and analyzed them as a single cohort in the present.…”
Section: Resultsmentioning
confidence: 99%
“…The study design and the details of J-EDIT are described in the article by Araki et al 12 in the present issue of the journal, and the details of the questionnaire for the nutritional survey are described in the article by Yoshimura et al 13 and Kamada et al 14 Following is a brief outline of the study: J-EDIT studied elderly type 2 diabetes patients, randomizing them to standard therapy or intensive therapy. It was a prospective randomized controlled trial that followed the patients for 6 years.…”
Section: Participants and Follow Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshimura et al (20) found that in elderly Japanese patients with type 2 diabetes increased energy intake per kilogram of standard body weight correlated with increase of BMI in men, but not in women. Intakes of soft drinks in both sexes and alcohol in women correlated with increase of BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, 12 we reported that characteristics of the dietary intake of diabetic patients suffering from obesity included a reduced intake of green vegetables and an increased intake of soft drinks and oils, and indulgences, such as alcohol.…”
Section: Introductionmentioning
confidence: 91%